Ubiquitous Learning with Online Project-Scratch Programming: Enhancing Student Engagement and Developing Problem-Solving Skills - Asmara, Andik; Ma, Hongbo (DPTE FT UNY, 2024)
Low student engagement in online learning is a challenge faced by many educators. The choice of tools used in online learning is also critical in determining whether they support ubiquitous learning for students. One tool that has proven effective in traditional (classroom) learning to increase engagement and problem-solving skills is Problem-Based Learning (PBL) on the Scratch platform. The purpose of this study is to examine whether PBL-Scratch can increase student engagement and perceptions of problem-solving skills in online learning. The study uses a quasi-experimental approach with a simple t-test analysis. The results indicate that PBL-Scratch can increase student engagement with a significance of 0.008 and perceived problem-solving skills in online learning with a significance of 0.025, making it a viable tool for ubiquitous learning.